To multiply the polynomials \((3x - 1)(2x + 4)\), we can use the distributive property (also known as the FOIL method for binomials).
Here’s the step-by-step calculation:
-
First: Multiply the first terms: \[ 3x \cdot 2x = 6x^2 \]
-
Outer: Multiply the outer terms: \[ 3x \cdot 4 = 12x \]
-
Inner: Multiply the inner terms: \[ -1 \cdot 2x = -2x \]
-
Last: Multiply the last terms: \[ -1 \cdot 4 = -4 \]
Now, combine all these results together: \[ 6x^2 + 12x - 2x - 4 \]
Next, combine like terms: \[ 6x^2 + (12x - 2x) - 4 = 6x^2 + 10x - 4 \]
So, the final result of multiplying \((3x - 1)(2x + 4)\) is: \[ \boxed{6x^2 + 10x - 4} \]